(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Junior school age (from 6-7 to 9-10 years old) is determined by an important external situation in a child’s life - entering school. Educational activity requires the development of higher mental functions - attention, memory, imagination. The attention, memory and imagination of a young school student are already gaining independence - the child learns to master special actions that allow him to concentrate on learning activities, remember what he sees or hear, and imagine something beyond what was before. learns previously accepted.